2011
DOI: 10.1258/mi.2011.011020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on menopausal symptoms

Abstract: Yoga is effective in reducing menopausal symptoms and should be considered as alternative therapy for the management of menopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 9 publications
3
50
1
2
Order By: Relevance
“…[33][34][35] Several things are worth noting about our findings. First, we found meaningful reductions in hot flashes despite attendance at the classes being suboptimal and lower than in other studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[33][34][35] Several things are worth noting about our findings. First, we found meaningful reductions in hot flashes despite attendance at the classes being suboptimal and lower than in other studies.…”
Section: Discussionmentioning
confidence: 61%
“…Two uncontrolled studies of yoga interventions found reductions in hot flashes. 31,32 Studies employing various control groups have also showed promising results, but have used very intensive yoga interventions (at least 5 days per week), 33,34 did not measure daily hot flashes, [33][34][35] combined the yoga intervention with education, 33 or lacked an attention control group. 36 The objective of the current study was to obtain preliminary data on the efficacy of yoga for reducing self-reported menopausal hot flashes in a randomized study that included an attention control group and measured daily hot flashes.…”
mentioning
confidence: 99%
“…Two uncontrolled studies of yoga interventions found reductions in hot flashes. 31,32 Studies employing various control groups have also showed promising results, but have used very intensive yoga interventions (at least 5 days per week), 33,34 did not measure daily hot flashes, 3335 combined the yoga intervention with education, 33 or lacked an attention control group. 36 …”
mentioning
confidence: 99%
“…Yoga has also been cited as a beneficial modality in the reduction of symptoms related to various autoimmune disorders, diseases, hormonal shifts, recovery processes (such as chemotherapy) and other stress-induced ailments (Curtis, 2011;Hedge, 2011;Joshi, 2011;Singh, 2011). Patients recovering from cancer found improved sleep, energy levels, mood, and reductions of cancer-related symptomology as compared to patients not receiving a yoga intervention (Bower, 2005;Cohen, 2004).…”
Section: The Science Of Yoga: Modern Researchmentioning
confidence: 99%